Women development and environment: Perspective from Malaysia - Mustafa, Maizatun; Mohamad, Nor Asiah (Serials Publications, 2012)
Women play a central role not only in economic and social life, but also in the development of sustainable approaches to natural resource management as was recognized at the United Nations Conference on Environment and Development. In Malaysia, women constitute almost half of the entire population and contribute to and participate significantly in the process of national building and economic development. Women also have particular strengths in contributing towards a more ecologically viable society and sustainable development. The purpose of this paper is to present a preliminary study of inter-linkages between women in Malaysia through resent statistics, and analyzes policies and national machinery related to women development and environment. At present, research literature on women's issues in Malaysia, especially those on the relationship between women and environment, has been limited in scope. It is hoped that findings on this paper will help increase awareness about the important role women play in societal development, environmental protection and help to promote the integration of environmental agenda within policy and strategies pertaining to women in Malaysia.